A percep????o dos ju??zes sobre o impacto da guarda compartilhada nas fam??lias que vivenciam a separa????o conjugal - Sena, Denise Pereira Alves de (2017)
The objective of this research was to investigate the perception and performance of the family jurisdiction judges, in Brasilia, in lawsuits involving shared custody of minor children, in cases of matrimony dissolution. The theoretical approach that justifies is structural family therapy, the Federal constitution, new Brazilian Civil code and laws related to shared custody. To achieve such a purpose, qualitative research was conducted with six standing judges, three women and three men. The instrument used was a semi-structured interview questionnaire. The collection was held at the respondent???s workplace. The information was processed through the IRAMUTEQ R software, that found six distinct classes that were subsequently renamed, grouped and, according to Bardin's (2011) definitions, consolidated into four categories. "Category 1 ??? Family: Yours and Mine " gathers the visions of the respondents about family, the ones they work and their own, demonstrating their perceptions about the influence of the family in the subject???s formation, as well as their personal experiences. For the respondents, the family can be composed of different arrangements, and their constituents may be related, or not. Their personal experiences were also made present to influence their way of deciding. The "Category 2 ??? Custody is Power" approached the subjects understanding of the custody???s power. The results pointed out that, for respondents, the shared custody balances the power of parents about decisions on children. They emphasize, that in this type of custody they share care and decisions, there is no direct relationship with the time that each parent stays with their children. The "Category 3 ??? Father and shared custody" showed that, despite the shared custody aims preserve the best interest of the child, the paternal figure was very empowered. "Category 4 ??? the judges who listen", although it was not contemplated by the Software, it appeared in the interviews when the magistrates reported that they are attentive to the quality of family relationships, careful with the fragility that families arrive for hearings and concerned to offer a humanized service to the former couple and children. The study demonstrates that the group interviewed is favorable to shared custody, realizing it as a legal response to the changes that society and consequently families are suffering, providing parental ties more suited to new family arrangements. Moreover, they are magistrates who act in a humanized manner in front of the weaknesses that divorce causes. This study aims to contribute to the understanding of the "young" law of shared custody, both for the legal area and for psychology.